Indoor Air Factors Affecting the Growth of Microorganism in an Indonesian Gas Company’s Dormitory - Sjahrul Meizar Nasri; Asduki D. Athari; Laksita Ri Hastiti; Fiori Amelia Putri (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Mold may affect the Indoor Air Quality (IAQ) in workplace dormitories. This study aims to investigate indoor air factors that affect molds growth in a dormitory of an LNG Company in Indonesia. Several indoor air determinant factors, including relative humidity, general temperature, wet temperature, dry temperature, air velocity, illumination, particulate matter, and carbon dioxide concentration were assessed against the growth of microorganism colonies. Methods: This study was a cross-sectional study using a 2 (two)-stage Andersen sampler based on NIOSH 0800 Bioaerosol Sampling Method for Indoor Air Quality for viable bioaerosol sampling. Bioaerosol samples were collected from 50 indoor, corridor, and outdoor sampling points. The total colony count for bioaerosols (TCC) was then determined (CFU/m3). Ten indoor air quality parameters, i.e., relative humidity, general temperature, wet temperature, dry temperature, air velocity, illumination, particulate matter, and carbon dioxide concentration, were measured. Results: The average mold colony concentration in the dormitory rooms was higher (703.1 CFU/m3) than the maximum standard issued by the Ministry of Health of the Republic of Indonesia (< 700 CFU/m3) while the relative humidity was very high (84.4% RH on average), with a direct relation between the humidity and the mold colony concentration. A significant correlation was also identified between mold colony concentration, wet temperature, and CO2 concentration. Conclusion: Significant correlations between bioaerosols, relative humidity, wet temperature, and indoor CO2 concentration indicate insufficient ventilation and poor indoor air quality in the dormitory.